2016
DOI: 10.1371/journal.ppat.1006088
|View full text |Cite
|
Sign up to set email alerts
|

MTOR-Driven Metabolic Reprogramming Regulates Legionella pneumophila Intracellular Niche Homeostasis

Abstract: Vacuolar bacterial pathogens are sheltered within unique membrane-bound organelles that expand over time to support bacterial replication. These compartments sequester bacterial molecules away from host cytosolic immunosurveillance pathways that induce antimicrobial responses. The mechanisms by which the human pulmonary pathogen Legionella pneumophila maintains niche homeostasis are poorly understood. We uncovered that the Legionella-containing vacuole (LCV) required a sustained supply of host lipids during ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(41 citation statements)
references
References 85 publications
(129 reference statements)
1
40
0
Order By: Relevance
“…Since TLR signaling is known also to activate mTORC1 (Abdel-Nour et al, 2014), we utilized BMMs from Myd88 −/− mice that are defective for TLR signaling. A previous report demonstrated that L. pneumophila activates mTORC1 in a Dot-dependent manner in Myd88 −/− macrophages (Abshire et al, 2016), but did not identify effectors responsible for mTORC1 activation. Remarkably, Myd88 −/− BMMs infected with the Δ flaA Δ7 strain exhibit decreased mTORC1 activity (as measured by phospho-S6K1) compared to BMMs infected with Δ flaA (Figure 1E).…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…Since TLR signaling is known also to activate mTORC1 (Abdel-Nour et al, 2014), we utilized BMMs from Myd88 −/− mice that are defective for TLR signaling. A previous report demonstrated that L. pneumophila activates mTORC1 in a Dot-dependent manner in Myd88 −/− macrophages (Abshire et al, 2016), but did not identify effectors responsible for mTORC1 activation. Remarkably, Myd88 −/− BMMs infected with the Δ flaA Δ7 strain exhibit decreased mTORC1 activity (as measured by phospho-S6K1) compared to BMMs infected with Δ flaA (Figure 1E).…”
Section: Resultsmentioning
confidence: 88%
“…Active mTORC1 represses autophagy and lysosome biosynthesis and stimulates translation initiation (Mohr and Sonenberg, 2012). L. pneumophila has previously been reported to modulate mTORC1 activity in infected cells, but no effectors responsible for this modulation have been identified (Abshire et al, 2016; Ivanov and Roy, 2013). …”
Section: Introductionmentioning
confidence: 99%
“…Within host cells, L. pneumophila forms the Legionella -containing vacuole (LCV), where it efficiently replicates before it exits the host cell by lysis. The LCV formation requires membrane biogenesis with sustained supply of host lipids during expansion (Abshire et al, 2016). In Legionella -infected MPs the lipid supply involves uptake of lipids from serum as well as de novo lipogenesis.…”
Section: Metabolic Changes Caused By Ibp/host Cell Interactionsmentioning
confidence: 99%
“…In contrast to the aforementioned pathogens, L. pneumophila promotes a Warburg-like metabolism in human monocyte-derived macrophages, which is a consequence of mitochondrial fragmentation and important for bacterial replication [149]. L. pneumophila actively sustains mTOR activity (through activation of PI3K by the effector proteins Dot/Icm), which may contribute to the promotion of glycolysis [150][151][152]. These examples illustrate that carbohydrate metabolism, in particular glycolysis, is strongly connected to mTOR signaling and that they are a target for various pathogens to modulate the immune response.…”
Section: Targeting Of Carbohydrate Metabolism By Pathogensmentioning
confidence: 99%